İkrah - Sevindik, Ersin (My University, 2008)
İkrah konulu yüksek lisans tez çalışmasında irade sakatlığı hallerinden biri olan ikrah kurumu tüm yönleriyle incelenmiştir. Tez 3 bölümden oluşmaktadır. Birinci bölümde; ikrahın tanımı, unsurları, türleri ve benzer kavramlardan ayrımı üzerinde durulmuştur. İkinci bölümde; hukukun ikraha bağladığı sonuçlar ve ikrahın ispatı incelenmiştir. Üçüncü bölümde ise kanunda özel düzenlemelerde yer bulan ölüme bağlı tasarruflarda ve kefalet sözleşmesinde ikrahın görünümü incelenmiştir.

Duress determined as one of the defects of edict has been fully studied in this master’s of degree thesis study which is subject of the duress. The thesis consists 3 sections. In the first section, description of duress, items, types and difference from allied subjects have been analyzed. In the second section, the results related to the duress in the law and the proof of the duress has been examined. In the third section, the appearance of the duress in the testamentary disposition and contract of surety mentioned in the legal private arrangements have been examined.
Keywords: Borçlar Hukuku; İkrah; İrade Sakatlığı